Plan estratégico para la distribuidora Camel de insumos Discamel Cia. Ltda. En la ciudad de Loja, período 2013 - 2018 - Loaiza Correa, Pablo Andrés (2014)
In the city of Loja enterprise management should be oriented towards the satisfaction of needs of families, for businesses it should emphasize the definition of its administrative, organizational and functional structure considering that companies have to compete with each other, processes, functional areas, prices, products, schedules, promotions and advertising to enable them to attract new customers and generate higher profits. The research takes as a general title: "STRATEGIC PLAN FOR DISTRIBUTION INPUT CAMEL DISCAMEL CIA. LTDA. CITY Loja, PERIOD 2013-2018 ". As a preliminary to this research work, a situational diagnosis of the distribution, which determines the various problems both operational and administrative nature, which together affect the daily distribution is made, it should be noted that these problems are the goals preliminary, they pretend to be corrected or deleted by the distributor. Regarding the method, the analytical, inductive, descriptive and inferential methods were used; research techniques were applied as the survey as well as the interview; the bibliography, confirming the development of this thesis. Also external factors of the distribution is analyzed by the matrix evaluation of external factors, the same who came to 2.67 points; where economic, political, social, technological and environmental factors were analyzed, the distributor also analyzed through Porter's five forces, and their direct or indirect impact on the normal development of the distribution, thus allowing to identify main opportunities and threats of the distributor, which allowed detecting that the distribution company has more market opportunities. Regarding the analysis of the internal factors of the distribution, 74 surveys with employees, 343 customer surveys and an interview to the Manager, data were tabulated and analyzed and interpreted then build matrix assessment was performed internal factors with a total of 2.34 points, results that determined the strengths and weaknesses of the distributor which the distributor considering the weaknesses against the strengths which may be adversely affecting the development of the same predominate. With the development of assessment matrices matrix allowing high impact strategic objectives to determine their courses of action for the distributor which became the support for the development of this work they are built: ➢ Increase market share at the provincial level. ➢ Improve customer ➢ Strengthen the corporate image. ➢ Increase diffusion to publicize the DISTRIBUTOR "CAMEL DISCAMEL CIA.LTDA INPUT" at the provincial level. In addition to the strategic plan and vision Tumacacori as fundamental pillars on which the distributor run your business goals and strategies with a total budget plan proposes $ 1,768.48. The main conclusions, recommendations, bibliography, and appendices are described in the final part of this work.